A Study of Donald Grantham’s Fantasy Variations: Broad Musical Connections in Core Theory Classes - Amy Carr-Richardson (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
This article contains analytical comments on Donald Grantham’s Fantasy Variations, which is based on George Gershwin’s Prelude II (“Blue Lullaby”), focusing on its pedagogical use in a core undergraduate theory class. It proposes encouraging students to make broad musical connections regarding tonality, temporality, and developmental process, across a wide range of musical repertoire. The article discusses the analysis of Fantasy Variations in relation to these topics: pedagogical transitions between the study of tonal and post-tonal music, the process of development, non-linear aspects of twentieth- and twenty-first century music, and musical borrowing.